Recent developments in paediatric neuraxial blocks - Ponde, Vrushali Chandrashekhar (Medknow Publications & Media Pvt Ltd, 2012)
Paediatric anaesthesia and paediatric regional anaesthesia are intertwined. Almost all surgeries unless contradicted could be and should be supplemented with a regional block. The main objective of this review is to elaborate on the recent advances of the central neuraxial blocks, such as application of ultrasound guidance and electrical stimulation in the pursuit of safety and an objective end point. This review also takes account of the traditional technique and understand the benefits as well the risk of each as compared with the recent technique. The recent trends in choosing the most appropriate peripheral block for a given surgery thereby sparing the central neuroaxis is considered. A penile block for circumcision or a sciatic block for unilateral foot surgery, rather than caudal epidural would have a better risk benefit equation. Readers will find a special mention on the recent thoughts on continuous epidural analgesia in paediatrics, especially its rise and fall, yet its unique importance. Lastly, the issue of block placements under sedation or general anaesthesia with its implication in this special population is dealt with. We conducted searches in MEDLINE (PubMed) and assessed the relevance of the abstracts of citations identified from literature searches. The search was carried out in English, for last 10 years, with the following key words: Recent advances in paediatric regional anaesthesia; ultrasound guidance for central neuraxial blocks in children; role of electrical stimulation in neuraxial blocks in children; complications in neuraxial block. Full-text articles of potentially relevant abstracts were retrieved for further review.